ANALISIS SOSIAL PETANI PADI SAWAH DI DESA RAMBAH BARU KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Romi Effendi; Evy Maharani; Ermi Tety (Fakultas Pertanian, Universitas Riau, 2019)
The purpose of this research is to analyze the social factors of rice farmers in Rambah Baru Village, Rambah Samo Sub-District, Rokan Hulu Regency. The education level of respondents is moderate because the average of education is junior high school. Residential condition of respondents is considered good and habitable considering the type of building, building status, building area, floor conditions, roof conditions, number of rooms, lighting equipment and the type of wall. The health of respondents is high because the average of respondents do not have a serious or dangerous disease. Most respondents have private vehicles for daily activities. The status of land ownership managed by the respondents is private property with the average of the managed area is 1-2 hectares.